IMPLEMENTATION OF BUSINESS MANAGEMENT FOR SUSTAINABLE DEVELOPMENT IN THE PHARMACEUTICAL INDUSTRY (CIPEEX, 2022)
IT WAS FROM THE MID-1980S THAT SUSTAINABLE DEVELOPMENT BEGAN. FROM THE CREATION OFAGENDA 21 IN ECO-92 THE SUBJECT BECAME AN AGENDA IN THE CORPORATE WORLD. HOWEVER, THE THEMENEEDS CONSTANT DISCUSSIONS AND ANALYSIS, AS THE RESULTS ARE OBTAINED IN THE LONG TERM. THE SEARCHFOR BALANCE REQUIRES CONNECTION BETWEEN THE PARTIES INVOLVED: COMPANY, STATE AND COMMUNITY. ITIS ARGUED THAT IN THE CORPORATE ENVIRONMENT IT IS NECESSARY TO INVEST IN THE IMPLEMENTATION OFPRACTICES THAT RESULT IN THE MINIMIZATION OF THE IMPACTS CAUSED BY INDUSTRIALIZATION AND THAT PUT ATRISK ENVIRONMENTAL SERVICES. THIS CAN BE ACHIEVED WITH A SUSTAINABLE BUSINESS MANAGEMENTMODEL, BASED ON THE CONCEPT OF CIRCULAR ECONOMY, REPRESENTING AN ALTERNATIVE PATH TO ACHIEVINGTHE SUSTAINABLE DEVELOPMENT GOALS (SDGS). BEING THE RELEVANT THEME FOR THE CONSERVATION ANDPRESERVATION OF NATURAL RESOURCES, THE IMPLEMENTATION OF A WASTE MANAGEMENT WITH FULL USE OFMATERIALS, MEETING IN AN INTEGRATED WAY THE LEGAL PARAMETERS DEFINED BY THE COMPETENT AGENCIES,AND SOCIO-ENVIRONMENTAL GAINS. THE 5RS METHODOLOGY SOLIDIFIES THE PROPOSED MODEL, ENTITLED"ZERO LANDFILL", MAINTAINING THE 100% INDEX OF WASTE SENT FOR RECYCLING OR RECOVERY AND INCREASESTHE REVENUE FOR INVESTMENTS IN THE LOCAL COMMUNITY. THE ENVIRONMENTAL STRATEGY SHOULD CONTRIBUTETO ECONOMIC AND SOCIAL DEVELOPMENT THROUGH A BUSINESS MANAGEMENT FOR SUSTAINABLEDEVELOPMENT GENERATING CONSISTENT BENEFITS. THE REDUCTION OF TOTAL WASTE BY 52%, INCREASE OFPROFIT AND SOCIO-ENVIRONMENTAL GAINS IN A PHARMACEUTICAL INDUSTRY, CHALLENGE EXISTING CONCEPTS INTHE LINEAR MANAGEMENT MODEL, INDICATING RELEVANCE OF THE CIRCULAR MANAGEMENT MODELIMPLEMENTED AND THE POSSIBILITY OF REPLICATION IN OTHER PRODUCTION PROCESSES.
Keywords: sustainable; circular economy; solid waste